2022
DOI: 10.1002/jso.26790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and oncological outcomes of primary female urethral cancer

Abstract: Investigation of the clinical features and treatment outcomes of primary female urethral cancer (FUC) at a single institution. Materials and Methods: We retrospectively reviewed 32 FUC patients during 1997-2017. We investigated preoperative risk factors predicting overall (overall survival [OS]) and recurrence-free survival (RFS) and reviewed clinical features, treatment modality, and oncologic outcomes according to pathology. The median follow-up duration and age was 56 months (range: 4-229) and 61 years (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As for the primary urethral carcinoma, its long-term survival after surgery is mainly referenced from the RARECARE (The project Surveillance of Rare Cancers in Europe) project [ 28 ] and the large SEER database [ 13 ] and results often cover early period. Certain recent studies also have reported differences in survival outcomes among different clinical stages and treatment modalities [ 29 , 30 , 31 , 32 ]. The prognostic outcome is determined largely by the clinical stage and pathological grade, distant metastasis presence and nodal stage, as well as type and modality of treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for the primary urethral carcinoma, its long-term survival after surgery is mainly referenced from the RARECARE (The project Surveillance of Rare Cancers in Europe) project [ 28 ] and the large SEER database [ 13 ] and results often cover early period. Certain recent studies also have reported differences in survival outcomes among different clinical stages and treatment modalities [ 29 , 30 , 31 , 32 ]. The prognostic outcome is determined largely by the clinical stage and pathological grade, distant metastasis presence and nodal stage, as well as type and modality of treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low incidence of PUCs, no statistics on survival of metastatic PUCs are available. Metastatic PUC lacks optimal treatment strategies based on current study data, chemotherapy is the main treatment, and multi-mode therapy is recommended ( 10 , 11 ). The efficacy of various therapeutic strategies, including immunotherapy and targeted therapy, has only been reported in a few individual cases.…”
Section: Introductionmentioning
confidence: 99%